Comparative voltammetric behaviour of the silver/silver oxide electrode prepared on vitreous carbon and silver substrates - Lopez Teijelo, Manuel (1988)
The voltammetric behaviour of vitreous carbon/chemically precipitated silver hydroxide layer and silver/electrochemically formed silver oxide layer electrodes are compared. As the former type of electrode is free from silver substrate contributions during the oxidation-reduction cycles (ORC) the voltammetric data indicate the occurrence of soluble Ag(I) species in the gel-like silver hydroxide matrix. Soluble species can be formed during the ORC as a consequence of AgOH formation at the early stages of the oxidation and reduction processes. Nucleation and growth of new phases produce a non-homogeneous layer structure and a decrease in the amount of active material participating in the ORC under preset conditions.